The Haudenosaunee Ohén:ton Karihwatéhkwen Thanksgiving Address: Moving Beyond the Havoc of Land Acknowledgements - Wemigwans, Jennifer; MacKay, Lanna (Engaged Scholar Journal, 2023)
This article aims to offer a broad theoretical engagement with the Haudenosaunee Ohén:ton Karihwatéhkwen (Thanksgiving Address) and the practice of giving thanks as a foundational Indigenous Knowledge education practice for elementary school age children. We propose a critical rethinking of the practice of the Land Acknowledgement and instead put forward the Thanksgiving Address as a way to center Indigenous Knowledge practices and education in school systems. We provide a brief overview of the history and practice of the Thanksgiving Address, and a critical examination of institutionalized land acknowledgments. The work of educators at the Jackman Institute for Child Study with land acknowledgements and the Thanksgiving Address offers insight into land and place-based pedagogical approaches that take up Indigenous knowledge education and challenges coopted practices of Indigenous education.